The impact of high nicotine concentrations on the viability and cardiac differentiation of mesenchymal stromal cells: a barrier to regenerative therapy for smokers - Gheisari, Maryam; Nosrati, Shadi; Zare, Shahrokh; Dara, Mahintaj; Zolghadri, Samaneh; Razeghian-Jahromi, Iman (Frontiers in Cell and Developmental Biology, 2024)
Background: Current treatment methods are not successful in restoring the lost cardiomyocytes after injury. Stem cell-based strategies have attracted much attention in this regard. Smoking, as a strong cardiovascular risk factor, not only affects the cardiac cells adversely but also deteriorates the function of stem cells. Since mesenchymal stem cells (MSCs) are one of the popular candidates in cardiovascular disease (CVD) clinical trials, we investigated the impact of nicotine on the regenerative properties (viability and cardiac differentiation) of these cells. Methods: MSCs were isolated from rat bone marrow and characterized based on morphology, differentiation capability, and the expression of specific mesenchymal markers. The MTT assay was used to assess the viability of MSCs after being exposed to different concentrations of nicotine. Based on MTT findings and according to the concentration of nicotine in smokers’ blood, the growth curve and population doubling time were investigated for eight consecutive days. Cells were treated with 5-azacytidine (an inducer of cardiac differentiation), and then the expressions of cardiac-specific markers were calculated by qPCR. Results: MSCs were spindle-shaped, capable of differentiating into adipocyte and osteocyte, and expressed CD73 and CD90. The viability of MSCs was reduced upon exposure to nicotine in a concentration- and time-dependent manner. The growth curve showed that nicotine reduced the proliferation of MSCs, and treated cells needed more time to double. In addition, the expressions of GATA4 and troponin were downregulated in nicotine-treated cells on day 3. However, these two cardiac markers were overexpressed on day 7. Conclusion: Nicotine decreased normal growth and reduced the expression of cardiac markers in MSCs. This aspect is of eminent importance to smokers with cardiovascular disease who are candidates for stem cell therapy.